Handbook of urbanization in India an analysis of trends and processes - Sivaramakrishnan K C; Kundu Amitabh; Singh B N (Oxford OUP, 2005)
This book comprehensively analyses urbanization trends in India using, for the first time, the 2001 Census data. It looks at definitional problems in the identification of urban settlements for comparative analysis. The realistic quantification of migrat
Keywords: India; Urbanization